The influence of mass media coverage and police integrity on public trust in police law enforcement institutions - Darafista, Firly; Sumardjoko, Bambang; Subowo, Arif (Universitas Tanjungpura, 2025)
This study aims to see the influence of mass media and police integrity on public trust in police law enforcement institutions. In today's digital era, mass media not only functions as a source of information, but also as a place for public opinion to be formed and widely disseminated, while the integrity of the Police is one of the factors in maintaining public trust. This study uses a type of research in the form of quantitative research with a correlational design. A sample of 270 respondents was selected purposively, namely people aged 17-45 years and domiciled in Surakarta City. Data were collected using a questionnaire that had previously gone through a process of testing the validity and reliability of the objectives so that the data collected was accurate and consistent. Data were analyzed using multiple linear regression to test the influence of the variables of mass media coverage and police integrity (independent) on the variable of public trust (dependent), data analysis was assisted using software in the form of SPPS version 27. The findings of this study reveal that each independent variable has an influence on the dependent variable. Media coverage contributes 13.9% to public trust. The variable of police integrity also shows a significant influence, contributing 59.8% to public trust. Meanwhile, the combined influence of media coverage and police integrity contributes 81% to public trust in law enforcement institutions, with the remaining 19% influenced by other factors not examined in this study.